Risk assessment for infected endocarditis in Staphylococcus aureus bacteremia patients: When is transesophageal echocardiography needed?. Issue 5 (1st August 2019) - Longobardo, Luca; Klemm, Sarah; Cook, Margaret; Ravenna, Valerie; Brummitt, Charles F; Mengesha, Tadele; Khandheria, Bijoy K
Abstract: Aims: Echocardiography is the main technique for the diagnosis of endocarditis in patients with Staphylococcus aureus bacteremia (SAB), but a consensus about performing transthoracic echocardiography or transesophageal echocardiography (TEE) as first-line tests is currently lacking. Recently, a new scoring system has been proposed by Palraj et al. to guide the use of TEE in this population. Our aim was to validate this scoring system or modify it, if necessary. Methods and results: Data from SAB patients admitted from 2012 to 2014 were collected. We tested the Palraj scores to stratify patients' risk for endocarditis. Moreover, we analyzed our population to identify any other possible clinical predictors of endocarditis not included in the score. Endocarditis was diagnosed in 38 of 205 patients (18.5%). Palraj's score was effective in the detection of patients at high risk of endocarditis. In addition, we identified the presence of cardiac devices, prolonged bacteremia and intravenous drug abuse (IVDA) as elements strongly correlated with endocarditis. Two scoring systems (Day-1 and Day-5) were derived including IVDA as a variable. Using a Day-1 cut-off value ≥5 and a Day-5 cut-off value ≥2, the 'modified Palraj's score' showed sensitivities of 42.1% and 97.0% and specificities of 88.6% and 32.0% for Day-1 and Day-5 scores, respectively. Conclusion: We modify and expand upon an effective scoring system to identify SAB patients at high risk for endocarditis in order to guide use of TEE. The inclusion of IVDA in the criteria for the calculation of the scores improves its effectiveness.